TAHAP KESEDARAN PEKERJA HUBUNGANNYA DENGAN SALAH LAKU GANGGUAN SEKSUAL DI TEMPAT KERJA - Isa, Khairunesa; Samad, Sazali (Journal of Techno-Social, 2012)
Sexual harassment in the workplace is an issue that needs to take seriously not only by the management of an organization even, employee awareness of the issue to some extent can help reduce cases involving sexual harassment among workers in the organization. In connection with the study in the form of a survey conducted to (i) identify the relationship between the level of employee awareness of the definition of sexual harassment by a factor of age, work experience, positions and gender in the workplace and (ii) identify the level of awareness of employees SAJ Holdings Sdn. Bhd. against sexual harassment in the workplace. Selection of the 130 respondents are using simple random sampling method while questionnaire used as an instrument for data collection. Data were analyzed using SPSS version 14.0. The findings show that the relationship between employees’ awareness in terms of the definition of sexual harassment by a factor of age, work experience, job title and sex is weak while the overall mean for the understanding of the definition of sexual harassment in terms of meaning and forms of sexual harassment are at a moderate level of 3:27. This finding is indicative of many workers who still are not aware of issues relating to sexual harassment in the workplace. Hence this study in particular, hope to help workers better understand the definitions of sexual harassment and that by understanding this disclosure issues involving sexual harassment in the workplace can be reduced.